Respostas
respondido por:
1
Explicação passo-a-passo:
Fórmula Resolvente: x=−b±b2−4ac−−−−−−−√2ax=-b±b2-4ac2a
x2+3x+4=0x2+3x+4=0
a=1a=1
b=3b=3
c=4c=4
x=−(3)±(3)2−4×(1)×(4)−−−−−−−−−−−−−−−−√2×(1)⇔x=-(3)±(3)2-4×(1)×(4)2×(1)⇔
x=−3±9−(16)−−−−−−−√2⇔x=-3±9-(16)2⇔
x=−3±−7−−−√2⇔x=-3±-72⇔
A equação de 2º grau não possui raízes reais!
Fórmula Resolvente: x=−b±b2−4ac−−−−−−−√2ax=-b±b2-4ac2a
2x2−4x+3=02x2-4x+3=0
a=2a=2
b=−4b=-4
c=3c=3
x=−(−4)±(−4)2−4×(2)×(3)−−−−−−−−−−−−−−−−−−√2×(2)⇔x=-(-4)±(-4)2-4×(2)×(3)2×(2)⇔
x=4±16−(24)−−−−−−−−√4⇔x=4±16-(24)4⇔
x=4±−8−−−√4⇔x=4±-84⇔
A equação de 2º grau não possui raízes reais!
Perguntas similares
5 anos atrás
5 anos atrás
5 anos atrás
7 anos atrás
7 anos atrás
7 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás